Effectiveness of using mebrocarbon mixtures against the Guatemalan potato moth in fresh potato tubers - Nyamtsu, E.; Klechkovskyi, Yu. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2025)
Goal. To determine the mebrocarbon mixtures with minimum consumption rates of methyl bromide effective against the Guatemalan potato moth (Tecia solanivora Povolny) and to develop fumigation regimes for the protection of fresh potato tubers from this pest.Methods. Bibliographic and analytical, laboratory, mathematical and statistical methods, as well as the method of analogous modeling were used in the research.Results. The technical effectiveness of mebrocarbon mixtures against potato moth was determined by the experimental method. Ten mixtures of methyl bromide with carbon dioxide and the standard were studied at a temperature of 4—8°C in four replicates, namely, five at a carbon dioxide temperature of 0°C when introduced into the fumigation space of the chamber and five at a temperature of 25°C. Technical methyl bromide was used as a standard. The standard consumption rate was 60 g/m3. The standard was introduced into the fumigation space of the chamber at a temperature of 25°C. The consumption rates of technical methyl bromide in the mixtures were gradually reduced by 30%, 40%, 50%, 60% and 70%, i.e., they were 42 g/m3, 36 g/m3, 30 g/m3, 24 g/m3 and 18 g/m3. For CO2, the consumption rate in the mixtures was 160 g/m3. The exposure time corresponded to 5 hours. After the treatment of fresh potato tubers with methyl bromide dosages of 42 g/m3, 36 g/m3, 30 g/ m3, provided that CO2 at a temperature of 0°C was introduced into the fumigation space, no live insects were found in the biotests, i.e. the technical efficiency was 100.00%. In tubers with biotests treated with mixtures with methyl bromide dosages reduced by 60% and 70% (24 g/m3 and 18 g/m3), an average of 1.5 and 5 live insects were found, respectively. At the same time, the technical efficiency was 98.50 and 95.00%, respectively. In the case when carbon dioxide was introduced into the fumigation space at a temperature of 25°C, no live insects were found in the biotests of the first four mebrocarbon mixtures, i.e., the technical efficiency was 100.00%. In the biotests of tubers treated with a mixture with a 70% reduction in CH3Br, i.e., with a consumption rate of 18 g/m3, two live insects were found. The technical efficiency was 98.00%.Conclusions. Taking into account the results of the research, it is advisable to use mebrocarbon mixtures in the fumigation of imported fresh potato tubers against the quarantine pest Tecia solanivora Pov. At the same time, there is a 2.5-fold reduction in the load of methyl bromide on the environment with 100% treatment efficiency and the absence of its phytotoxic effect on the treated plant products.